Friction Performance and Mechanism of the Molybdenum Disulfide Film in Carbon Dioxide Atmosphere. (8th June 2020) - Chen, Shibo; Huo, Lei; Lu, Zhaoxia; Pu, Jibin; Hou, Baorong
Abstract : In this work, the tribological properties of MoS2 films were investigated in air, vacuum and carbon dioxide environments by means of experiments and First-principles calculations. The results showed that the MoS2 film had the lowest and more stable coefficient of friction in carbon dioxide atmosphere than that in other environments. The MoS2 film usually loses some S atoms to produce S-vacancy defects during sputtering deposition, which can be filled by carbon dioxide molecules in a way of chemisorption. The strong repulsive force always existed at the interfaces of MoS2 adsorbed with carbon dioxide molecules, which was responsible for the low friction coefficient of MoS2 films in carbon dioxide. In the future, the MoS2 film is likely to be widely used on Mars that is well known for its CO2 -rich atmosphere.